Internet of Things based Greenhouse - Chakanyuka, Ashley Nash C. (Midlands State University, 2020)
The purpose of this study was to develop a system that can help farmers and garden enthusiasts to manage their greenhouses by the use of a network of sensors connected together and controlled by a central hub. This complies with the world vision of connecting as much devices together as possible that has been dubbed the Internet of Things phenomenon. The system makes use of sensors that a controlled by a central controller that sends the data to a server that streams the data to an android application that allows the user to view minute by minute sensory values of the greenhouse sensors. In a country like Zimbabwe were the rain patterns are changing due to global warming it could be a great asset, since it has the ability to measure the amount of water used by plants can help optimize the use of the resource and it will allow farmers to venture into producing crops that are not native to the country since a ventilation system will be used to control the climate of the greenhouse (climate control).